Living with Uncertainty While Maintaining Educational Values (A Critical Overview). Issue 13 (December 2013) - Barrow, Robin
This paper endorses the overall argument of the preceding contributions. It argues for an approach to teacher education focused more strongly on the nature of the educational enterprise and the why, wherefore and how of teaching specific subjects. The importance of distinguishing between the provisional nature of knowledge claims and relativism is stressed, as is the distinction between the uncertain and the arbitrary.